Konsep Pendidikan Gender Dalam Pemikiran Asma Barlas: Telaah Filsafat Pendidikan Islam - Janna, Siti Riadil (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
This research seeks to examine more deeply related to the concept of gender education in Asma Barlas' thought, which is then examined through the philosophy of Islamic education. As a literature research, research data is obtained from various scientific literature for further processing and analysis. The results of the study show that the concept of gender education in Asma Barlas' thought is very relevant to the philosophical framework of Islamic education philosophy as a forum for the formation of values that are critical, constructive, and transformative. Asma Barlas' thought, which emphasizes the reading of religious texts that have been trapped in patriarchal doctrine, can be one of the models for the development of a more critical, constructive, and transformative philosophy of Islamic education in the future.